2012
DOI: 10.1007/s00011-012-0455-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between TNFAIP3 gene polymorphisms and rheumatoid arthritis: a meta-analysis

Abstract: This meta-analysis confirms that the TNFAIP3 polymorphisms are associated with RA susceptibility in different ethnic groups, namely, in Europeans for rs6920220 and in Asians for rs10499194.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 29 publications
3
26
1
1
Order By: Relevance
“…Previously, Lee et al also performed a meta-analysis to investigate TNFAIP3 gene rs10499194 polymorphism with RA susceptibility [25]. They indicated that rs10499194 polymorphism was not associated with RA susceptibility [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, Lee et al also performed a meta-analysis to investigate TNFAIP3 gene rs10499194 polymorphism with RA susceptibility [25]. They indicated that rs10499194 polymorphism was not associated with RA susceptibility [25].…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that rs10499194 polymorphism was not associated with RA susceptibility [25]. Stratification analyses of ethnicity in their meta-analysis [25] suggested that rs10499194 polymorphism was weakly associated with an increased risk of RA among Asian populations, while no association was observed among Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Оба полиморф-ных маркера (rs6920220 и rs10499194), расположенные в гене TNFAIP3 и показавшие связь с ЮИА, также показа-ли сильно выраженную ассоциацию с РА [39]. Кроме того, найдены различные варианты гена TNFAIP3, вовлеченные в патогенез системной красной волчанки, псориаза, целиа-кии, что свидетельствует о предрасполагающей роли этого гена в патогенезе многих аутоиммунных болезней.…”
Section: гены предрасположенности к ювенильному идиопатическому артриunclassified